Empire of ice and stone : the disastrous and heroic voyage of the Karluk - Levy, Buddy, 1960- (St. Martin's Press, 2022)
"The true, harrowing story of the ill-fated 1913 Canadian Arctic Expedition and the two men who came to define it. In the summer of 1913, the wooden-hulled brigantine Karluk departed Canada for the Arctic Ocean. At the helm was Captain Bob Bartlett, considered the world's greatest living ice navigator. The expedition's visionary leader was a flamboyant impresario named Vilhjalmur Stefansson hungry for fame. Just six weeks after the Karluk departed, giant ice floes closed in around her. As the ship became icebound, Stefansson disembarked with five companions and struck out on what he claimed was a 10-day caribou hunting trip. Most on board would never see him again. Twenty-two men and an Inuit woman with two small daughters now stood on a mile-square ice floe, their ship and their original leader gone. Under Bartlett's leadership they built make-shift shelters, surviving the freezing darkness of Polar night. Captain Bartlett now made a difficult and courageous decision. He would take one of the young Inuit hunters and attempt a 1000-mile journey to save the shipwrecked survivors. It was their only hope. Set against the backdrop of the Titanic disaster and World War I, filled with heroism, tragedy, and scientific discovery, Buddy Levy's Empire of Ice and Stone tells the story of two men and two distinctively different brands of leadership: one selfless, one self-serving, and how they would forever be bound by one of the most audacious and disastrous expeditions in polar history, considered the last great voyage of The Heroic Age of Discovery"--